STRATEGI PEMBELAJARAN MATEMATIKA BERBASIS PENGALAMAN NYATA PADA ANAK USIA DINI DI TK 08 PENATO’I KOTA BIMA - Faridah; Nurul Arifah; Siti Inganah (STKIP Subang, 2025)
This study aims to determine whether the implementation of real-life experience-based mathematics learning can have an impact on improving the learning abilities of children at Penato'i Kindergarten 08 in Bima City. This study uses a qualitative method involving a field research approach. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used the stages developed by Miles and Huberman. The results showed that teachers designed mathematics learning activities related to children's daily experiences, such as counting objects around them, grouping colours and shapes, and measuring length using simple tools. These real-life activities made children more active, enthusiastic, and able to understand mathematical concepts more easily in concrete terms. In addition to improving cognitive understanding, learning based on real-life experiences also had a positive impact on children's creative and social development, such as increased self-confidence, ability to work together, and independence in learning.